A new auspicious scaffold for small dyes and fluorophores - Volpi, Giorgio; Garino, Claudio; Priola, Emanuele; Barolo, Claudia (Dyes and pigments, 2022)
An unprecedented chromophore, based on a nitrogen fused tricyclic heterocycle, is presented. This prototype molecule can be considered a “rigidified” monomethine cyanine dye and the central core is isoelectronic to pyridine-based BODIPY analogues, such as boron difluoride dipyridylmethene. The chromophore was synthesized and its photophysical properties examined. The new molecule can be considered the starting point to develop dyes, fluorophores or dual-emission fluorescent probes with excitation window in the green region of the spectrum.